Latest Advances In Atomic Cluster Collisions: Fission, Fusion, Electron, Ion And Photon Impact - Connerade Jean-Patrick (World Scientific Publishing Company, 2004)
This comprehensive volume surveys the general aspects of atomic cluster science and outlines some of its important new challenges. It begins by detailing the recent advances in the understanding of structure and the essential properties of selected atomic cluster systems, fullerenes and confined atoms. Recent advances in the field of photo processes involving atomic clusters and fullerenes are discussed, and an entire chapter is devoted to the problem of fission dynamics of atomic clusters, presenting parallels with similar processes in nuclear physics. The book goes on to describe the problems of electron-cluster collisions with special emphasis on polarization and collective excitation effects. The important area of the behavior of atomic clusters in laser fields is considered; the ionization, collective dynamics of electrons in the system in the presence of the laser field, and the laser induced dynamics of molecules and clusters are thoroughly described. Finally, a broad spectrum of problems in the area of ionic collisions with fullerenes and metal clusters is covered -- from both experimental and theoretical points of view -- and the results of the most recent measurements are reported. The concluding chapter takes a careful look at the interaction of an atomic cluster with a surface. The problems of cluster deposition and formation at a surface as well as collision processes involving clusters deposited at a surface are considered through a number of illustrative examples.